Use of citizen science datasets to test effects of grazing exclusion and replanting on Australian woodland birds. Issue 7 (10th December 2021) - Gibson, Michelle; Maron, Martine; Taws, Nicki; Simmonds, Jeremy S.; Walsh, Jessica C.
Abstract : Around the world, woodlands have been cleared for agricultural production and their bird communities are in decline. To reverse these declines and foster bird community resilience, government agencies, non‐government organizations, and private landholders have implemented restoration actions, commonly including grazing exclusion and replanting. These actions are rarely implemented in an experimental framework, making it difficult to measure their effectiveness. However, ecological monitoring datasets, and citizen science datasets in particular, can provide useful opportunities for measuring effects of restoration actions and act as a baseline upon which adaptive management can be built. We examined the effect of revegetation actions on the terrestrial bird community in Australia's south‐eastern temperate woodlands using long‐term, community‐collected monitoring datasets. We explored the response of bird abundance, species richness, and a newly developed index of ecological community condition, to grazing exclusion and replanting over a 20‐year period using an uneven control‐impact study design. Grazing exclusion plus replanting had strong positive effects on all three bird community metrics, which increased with time, compared to control sites where neither action occurred. Bird abundance, but not species richness or community condition, increased over time with grazing exclusion alone, while control sites with continued grazing and no replanting showed no change in all three measures. We demonstrate that citizen science datasets with imperfect study designs can be used to gain insights on conservation action effectiveness and highlight the value of metrics that capture information about community condition more precisely than just abundance or species richness.